Application of the Rapid Application Development Method to Analyze the MBKM Information System at Prima Indonesia University - Wijaya, Teddy Chandra Wijaya; -, Vanness; -, Jefry; Tania, Andre; K.Nababan, Marlince Novita (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Independent Campus (MBKM) is an innovation carried out by the Ministry of Education, Culture and Research to produce graduates who are ready to face rapid technological advances and one of the campuses that has implemented it is Universitas Prima Indonesia (UNPRI), where students have difficulty with UNPRI MBKM activities. to take part in MBKM activities due to misinformation and lack of information. To improve the MBKM activity process, researchers will re-analyze the MBKM management information system, namely based on the RAD (Rapid Application Development) model. By implementing the Rapid Application Development (RAD) model in the MBKM program at Prima Indonesia University, it was able to analyze according to the administrator's needs, where the RAD model found that the analysis of business processes from student track records was incomplete, and for further research it was necessary to develop stakeholders who were willing to join with the campus.